2014
DOI: 10.1155/2014/190139
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Gill Filaments and Secondary Lamellae ofCirrhinus mrigalaExposed to “Nuvan,” an Organophosphorus Insecticide

Abstract: The alterations in the epithelium of the gill filaments and the secondary lamellae of the gills ofCirrhinus mrigala, on exposure to “Nuvan,” have been explored in the present investigation using light and scanning electron microscopy. The fishes were exposed to two sublethal concentrations, 5 mg/L and 15 mg/L, of “Nuvan.” The changes are more rapid and intensive at higher concentration than at lower concentration, suggesting that the changes are dose dependent. Increase in thickness of epithelium covering seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Following the infection of ionocytes, in more advanced stages of the infection we observed hyperplasia of the lamellar epithelium and proliferation of epithelial cells. Proliferation of undifferentiated epithelial cells in this area is commonly reported in fish exposed to heavy metals [ 41 , 42 , 43 , 44 ], drugs [ 45 ] and organic compounds [ 46 , 47 ], as well as during different kinds of gill infections [ 48 , 49 ], where it has been correlated with the downregulation of p53 tumour suppression protein and the overexpression of proliferating cell nuclear antigen PCNA [ 50 ]. This reaction was suggested to be a fish immune strategy aiming to increase the width of the thin tissue layer that separates the shallow respiratory capillaries from the harmful agent, preventing its permeation into the blood stream [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following the infection of ionocytes, in more advanced stages of the infection we observed hyperplasia of the lamellar epithelium and proliferation of epithelial cells. Proliferation of undifferentiated epithelial cells in this area is commonly reported in fish exposed to heavy metals [ 41 , 42 , 43 , 44 ], drugs [ 45 ] and organic compounds [ 46 , 47 ], as well as during different kinds of gill infections [ 48 , 49 ], where it has been correlated with the downregulation of p53 tumour suppression protein and the overexpression of proliferating cell nuclear antigen PCNA [ 50 ]. This reaction was suggested to be a fish immune strategy aiming to increase the width of the thin tissue layer that separates the shallow respiratory capillaries from the harmful agent, preventing its permeation into the blood stream [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in Hoven’s carp, Leptobarbus hoevenii , a temperature increase of 4 °C above the optimal range decreased gill epithelial thickness [ 6 ]. Several studies have shown an increase in gill epithelial height following exposure to toxicants and environmental pollutants [ 32 , 33 , 34 ], suggesting that such changes may serve as a general protective mechanism under suboptimal environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The studies on gills showed the detachment of basal epithelial membrane in gills compared to control which might have lead to death of the fish. Several studies have been made in the past on the histological organization and physiology of gills in a variety of fishes [18]. Gills are very important for the fishes since they are the main site of gaseous exchange and involved in osmoregulation [19].…”
Section: Discussionmentioning
confidence: 99%